(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Glushko M. Keywords: logicality, qualities of speech, accuracy, fractal radial matrices. This article focuses on the identification of components in the concept ‘logicality’ and the description of its place in the system of other qualities of speech. This paper puts forward the idea of applying fractal radial matrices for the analysis. This method allows distinguishing four basic speech qualities: beauty, clarity, accuracy, relevance and give them a universal characteristic. The main interest of the author aims at studying the element ‘accuracy’, which splits into four categories (accuracy, conclusiveness, consistency, consistency), each of which is associated with the concept ‘logicality’.